Education for the Dramatic Play (EPJD): a French theater school - Scheffler, Ismael (Revista Brasileira de Estudos da Presença, 2022)
The article aims to comprehend the Parisian theater school Education for the Dramatic Play [Éducation Par le Jeu Dramatique] (EPJD), active between 1946 and 1952. Through bibliographical and documentary research, it was It is possible to reconstruct some information, to understand historical and theatrical contexts, to know aspects of functioning, pedagogical proposals and networks of influences. The EPJD was headed by Jean-Marie Conty (1904-1999) and had the collaboration of leading French theater and dance personalities. It had influence in other countries, including Brazil, notably through Maria Clara Machado. The EPJD was the first school in which Jacques Lecoq (1921-1999) taught. Thus, considerations of EPJD with Lecoq are established.